2014
DOI: 10.1080/19440049.2014.918283
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure and risk assessment to lead of the population of Jiangsu province, China

Abstract: The paper's main purpose is to estimate the dietary exposure to lead for the inhabitants of Jiangsu province, China. Lead concentration data were obtained from the national food contamination monitoring programme during 2007-10. Food samples (n = 2077) were collected from 23 food categories in Jiangsu province. Consumption data were derived from Chinese national nutrition and health survey in 2002, which included 3938 inhabitants from 1451 households in Jiangsu province. Concentration data were combined with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…The mean concentration of Cd in this study was 0.0085 mg/ kg. Milk and dairy products were the lowest Pb contaminated foods in Jiangsu Province in 2014; the mean concentration was 0.036 mg/ kg (Jin et al, 2014), which was higher than the average Pb content (0.0189 mg/kg) in all foodstuffs found in this study. The highest content of As in this study was cod, with a mean concentration of 1.403 mg/kg.…”
Section: Discussioncontrasting
confidence: 67%
“…The mean concentration of Cd in this study was 0.0085 mg/ kg. Milk and dairy products were the lowest Pb contaminated foods in Jiangsu Province in 2014; the mean concentration was 0.036 mg/ kg (Jin et al, 2014), which was higher than the average Pb content (0.0189 mg/kg) in all foodstuffs found in this study. The highest content of As in this study was cod, with a mean concentration of 1.403 mg/kg.…”
Section: Discussioncontrasting
confidence: 67%
“…Sun et al [50] estimated the dietary intake of lead in Jiangsu Province using the diary study method and found a mean intake of 2.75 μg/kg bw/day for children aged 2–6 years and 1.55 μg/kg bw/day for the general population. Jin et al [44] re-estimated the dietary lead exposure in Jiangsu using new contaminant surveillance data, and their results indicated a dietary lead intake of 3.019 μg/kg bw/day in children aged 2–6 years and 1.742 μg/kg bw/day in the general population. Fan et al [51] reported dietary lead exposure values for children aged 2–6 years and for the general population in Shaoxing of 1.87 and 1.14 μg/kg bw/day, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A dietary lead exposure assessment in the Chinese population conducted by Li et al yielded MOE values of 0.1 for those aged 2–12 years, 0.7 for those aged 13–19 years, and 0.7–0.9 for those at least 20 years of age [34]. For the residents of Jiangsu province, the MOE values for the mean lead exposure were found to be 0.272 for those aged 2–6 years and 1.031 for those aged 18–80 years [44]. The MOE values of dietary lead exposure in Shaoxing were found to be 0.32–0.35 for those aged 2–6 years, 0.49–0.59 for those aged 7–17 years, and 1.3–1.7 for those aged ≥18 years [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among young children living in the US and Mexico, lead concentration in candy was associated with BLLs. 56,57 Others have also found the potential for lead exposure from foods, including vegetables and cereals, [58][59][60] with some home-grown vegetables, particularly from urban gardens, being one possible source of exposure. 61 The Food and Agriculture Organization of the United Nations/ World Health Organization guidance on food-based lead exposure, set at a provisional tolerable monthly intake of 25 mg/ kg body weight, is now considered inadequate to protect human health.…”
Section: Food As a Source Of Lead Exposurementioning
confidence: 99%